Gaya Kelekatan dan Emotional Abuse pada Dewasa Awal Berpacaran - Khoiriah, Cleopatra (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2021)
This study aims to determine the style of attachment and emotional abuse in early adults who are dating in Bekasi. The subjects of this study were early adults with characteristics of: 1) being 18-25 years old; 2) being dating; 3) domiciled in Bekasi. The research method used descriptive qualitative with data collection techniques using interviews and observations of 3 subjects, as well as supporting data from the survey results of 64 respondents. The data retrieval technique uses accidental sampling. The results of the study revealed that the study subjects received emotion abuse such as restraint from daily associations and on social media, mentions with harsh words, and body shaming so that the subject felt uncomfortable and depressed, but nevertheless the subject still had attachment to the partner with a type of safe attachment style, avoidance and anxiety. This study recommends discussing assertively with the partner the feelings of emotional abuse that are felt, as well as rethinking the continuity of the relationship if without a commitment to change, this is because starting from a circle of emotional violence will continue to physical and verbal violence.